A case report of synchronous primary malignancy: Papillary thyroid carcinoma and non-Hodgkin’s lymphoma (Indian Journal of Case Reports, 2019)
Multiple primary malignancies involving papillary thyroid carcinoma and non-Hodgkin’s lymphoma (NHL) is an extremely unusual event. Here, we report the case of a 70-year-old man presented with high-grade fevers and abdominal discomfort and were found to have pancytopenia. He had generalized lymphadenopathy, hepatosplenomegaly, goiter, and tracheal shift. Biopsy of the left cervical lymph node was positive for papillary carcinoma of the thyroid. He underwent excision biopsy of axillary lymph node which was suggestive of high-grade NHL. The patient was started on chemotherapy (R-CHOP) and his fevers resolved promptly. He then underwent total thyroidectomy and the histopathology of the thyroid gland post-operative showed papillary carcinoma. The second primary malignancy is a second malignant neoplasm occurring in a patient with known cancer. This case highlights the unusual synchronous occurrence of the papillary carcinoma of thyroid and NHL and the diagnostic challenges involved in such cases.